The Mitochondrial Message-specific mRNA Protectors Cbp1 and Pet309 Are Associated in a High-Molecular Weight Complex - Krause, Kirsten (The American Society for Cell Biology, 2004)
In Saccharomyces cerevisiae, the nuclear-encoded protein Cbp1 promotes stability and translation of mitochondrial cytochrome b transcripts through interaction with the 5′ untranslated region. Fusion of a biotin binding peptide tag to the C terminus of Cbp1 has now allowed detection in mitochondrial extracts by using peroxidase-coupled avidin. Cbp1 is associated with the mitochondrial membranes when high ionic strength extraction conditions are used. However, the protein is easily solubilized by omitting salt from the extraction buffer, which suggests Cbp1 is loosely associated with the membrane through weak hydrophobic interactions. Gel filtration analysis and blue native PAGE showed that Cbp1 is part of a single 900,000-Da complex. The complex was purified using the biotin tag and a sequence-specific protease cleavage site. In addition to Cbp1, the complex contains several polypeptides of molecular weights between 113 and 40 kDa. Among these, we identified another message-specific factor, Pet309, which promotes the stability and translation of mitochondrial cytochrome oxidase subunit I mRNA. A hypothesis is presented in which the Cbp1–Pet309 complex contains several message-specific RNA binding proteins and links transcription to translation of the mRNAs at the membrane.